The dangers of distrustful complacency: Low concern and low political trust combine to undermine compliance with governmental restrictions in the emerging Covid-19 pandemic. (January 2022) - Lalot, Fanny; Heering, Maria S.; Rullo, Marika; Travaglino, Giovanni A.; Abrams, Dominic
People comply with governmental restrictions for different motives, notably because they are concerned about the issue at hand or because they trust their government to enact appropriate regulations. The present study focuses on the role of concern and political trust in people's willingness to comply with governmental restrictions during the Covid-19 pandemic. We conducted a survey amongst Italian and French participants ( N = 372) in March 2020 while both countries had imposed full lockdown. Moreover, a subsample of participants reported on their actual levels of compliance one week later ( N = 130). We hypothesised that either concern or trust should be sufficient to sustain participants' willingness to comply and actual behaviour, but that the absence of both (distrustful complacency) would reduce compliance significantly. Results supported this hypothesis. We discuss implications of the interaction between concern and trust for public behaviour strategies as the pandemic progresses.